Tree species distribution and phylogenetic diversity across southern South America - Vanessa Leite Rezende (Frontiers of Biogeography, 2017)
The present-day southern South American flora comprises a group of lineages with southern temperate affinities, which have been suggested to have evolved during and after the breakup of Gondwana, as well as a group of Neotropical elements which are largely found in northern South America. Here, I aim to assess the floristic coherence of the main vegetation types that inhabit this region and determine the principal drivers of variation in the evolutionary diversity of these forest communities. I compiled a database of 3662 species of shrubs and trees at 781 sampling sites spread over six countries in South America. To understand the vegetation types that occur in the region I conducted clustering and ordination analyses. I then compared the defined vegetation types using taxonomic distinction, indicator species and phylogenetic diversity analyses. My results indicated a high diversity of vegetation types in terms of woody floristic composition, with a large number of indicator species, many of which are endemic. Contradicting the idea that temperate floras are recently derived and evolutionarily poor subsets of tropical floras, I demonstrated that the forests of the far south of South America are characterized by exceptional evolutionary diversity.